Euthanasia as Medical Therapy in Canada - Lemmens, Trudo (The Hastings Center report, 2025)
This commentary argues that recent reports of an Ontario coroner's office's MAiD Death Review Committee confirm how Canada's euthanasia regime has normalized ending of life as a form of therapy, often for only indirectly health-related suffering. The author, a member of the committee, illustrates with some of the cases how access to death rather than protection against premature death appears to be prioritized, often after very basic capacity and informed consent procedures by health professionals with limited training in relevant end-of-life health care.